Cellulase production by thermophilic Bacillus licheniformis 2D55 and its application for recovery of fermentable sugar from rice husk - Olanike, Kazeem Muinat (2018)
Fermentable sugar production from various agro-waste biomass via enzymatic saccharification using mesophilic fungi cellulase has been the issue of interest for many researchers. However, research carried out using thermophilic bacterial cellulase for sugar production are limited. Cellulases, chemical pretreatment and enzymatic saccharification required for sugar production are very costly and often result in low sugar yield, thereby affecting the overall economics of the bioconversion process. Hence, the main aim of this study was to isolate, characterize and enhance the production of cellulolytic enzyme complex (CMCase, FPase and β-glucosidase) and Xylanase from agro-waste mixture (a mixture of untreated sugarcane bagasse and pretreated rice husk) by a locally isolated thermophilic Bacillus licheniformis 22D55 and utilize the crude thermostable cellulase enzyme for sugar production through enzymatic saccharification of rice husk subjected to high pressure steam pretreatment. Cellulose degrading bacterium isolated from oil palm empty fruit bunch-chicken manure compost was identified by morphological, biochemical and 16S rRNA test and known as B. licheniformis 2D55. In basal medium with microcrystalline cellulose as carbon source, the bacterium produced cellulase at 50C within 18-24 h. Among the various untreated and sodium hydroxide (NaOH) pretreated agro-waste biomass used, agro-waste mixture comprising of untreated sugarcane bagasse and pretreated rice husk results in overall improvement in the cellulolytic enzyme complex with CMCase at 0.37 U/mL, FPase at 0.29 U/ml, β-glucosidase at 0.006 U/mL and xylanase at 0.98 U/mL. The SEM image reveal deformity in bacteria cell grown on NaOH pretreated sugarcane bagasse only, which resulted in the low performance of the bacteria for cellulase production on the substrate. Effect of nutritional and physicochemical factors were investigated for enhancing cellulase production. The CMCase, FPase, and β-glucosidase activities increased by 77.4-folds, 44.3-folds, and 10-folds, respectively. The crude enzyme was highly active and stable over broad temperature (50 to 80°C) and pH (3.5 to 10.0) ranges with optimum temperature at 65°C and 80ºC for CMCase and FPase, respectively. While the optimum pH for CMCase and FPase was 7.5 and 6.0, respectively. An operational condition was developed for high pressure steam pretreatment (HPSP) of rice husk for fermentable sugar recovery through enzymatic saccharification. The pretreatment at 200°C/1.85 MPa for 7 min was found to effectively enhance cellulose content of the rice husk. The scanning electron micrograph (SEM), fourier transform infrared (FTIR) and x-ray diffraction (XRD) analysis expressed effectiveness of the pretreatment. A two-step saccharification of pretreated rice husk at 60°C yielded reducing sugar at 0.581 g/g substrate that was equivalent to 73.5% saccharification. Therefore, the strain B. licheniformis 2D55 has the potential of utilizing agro-waste mixture for higher cellulolytic enzyme production. The thermostable nature of the cellulase contributed to the efficient release of fermentable sugars at higher temperature. The application of high pressure steam pretreatment and two-step enzymatic saccharification provides greener technology and improve the fermentable sugar production. The results of this study could contribute to future research in thermophilic bioprocessing rice husk with the application of thermostable cellulase producing bacterium for improving biomass-sugar conversion.